Предмети з обробленої кістки з городища Радичівське 3 на р. Десна (за матеріалами досліджень 1991—1992 рр.) - Сергєєва, М.С.; Кравченко, Р.А. (Археологія і давня історія України, 2021)
До наукового обігу введено й проаналізовано вироби з кістки з багатошарового поселення Радичівске 3 (Коропський р-н Чернігівської обл.), виявлені в ході досліджень 1991—1992 рр. Вироби походять з
об’єктів роменської культури і культурного шару.
Переважна більшість знахідок репрезентована
знаряддями праці з загостреним функціональним
кінцем. У колекції є також лощило з ребра, кістяний предмет (застібка або функціональна деталь
складного пристрою) і амулет з ікла ведмедя. 2 кістки коня з природним загостренням без слідів використання, які також походять з колекції, не є знаряддями. Загалом склад виробів з кістки є звичайним для слов’янських пам’яток. Вони могли належати особам, які займалися обробкою тваринної сировини шкіри і хутра. The bone objects from the multi-layered settlement
Radychivske 3 (Korop district, Chernihiv region) are
introduced into scientific circulation and analyzed in
the paper. They have been found during the excavations
in 1991—1992. The items come from objects of
Romny culture (structures and pits) and from the cultural
layer.
Most of the finds are pointed tools. Thirteen of them
can be interpreted as tools for treating of seams or for
weaving and 2 are piercing tools. The collection also
contains two horse bones with a natural sharpening
with no traces of use. Their interpretation as tools is
problematic. The collection also includes the polish tool
made of rib. In addition, in the collection of treated
bone there is a workpiece made of compact bone.
The bone object with a through hole in its middle
part can be interpreted as a detail of complex device,
perhaps the lock or clasp. Its analogy is the bone item
of similar shape from Kyiv. The item from Radichiv
was found in the cultural layer. The conditions of the
find make it difficult for dating but the Kyiv parallel
allows us to date it to the Slavic (Romny culture) or
Old Rus time.
The collection also includes the bear’s fang amulet.
Such amulets were common during Slavic and Old
Rus time. They occur mainly from the sites of the 9th—
10th centuries although in general they are found both
earlier and later than the time in question.
All the tools were made from the bones of domestic
animals, mostly cattle. Horse bones and single specimens
of bones of pig and small cattle were also identified.
So the manufacture of such products was based on
materials at hand.
In general, the set of bone products is common for
Slavic sites. Considering that, if necessary, each artisan
could make the bone items for himself, we can assume
that they belonged to persons who were engaged
in the treatment of animal raw materials, primarily of
leather and fur.